INCREASED URGENCY IN SCOUTING TO FORM THE CHARACTER OF MUTUAL COOPERATION - Haniva Batubara; Devina Aulia Rahmi; Nur Indah Syafitri (Journal of Quality Islamic Education Research, 2024)
The type of research used in this research is qualitative research. The data collection techniques used in this research are as follows: (1) Observation (Observation, documentation and traiangulation. The results of research at the level of scouts forming the character of mutual cooperation can also be interpreted in the context of community empowerment because they can become social capital to form institutional strength at the community, state community and cross-national and Indonesian state levels in realizing prosperity. This is also because mutual cooperation contains the meaning of collective action to struggle, self-governance, common goals and sovereignty. In perspective socio-culturally, the value of mutual cooperation is a spirit that is manifested in the form of individual behavior or actions carried out selflessly (expecting something in return) to do something together for the common good or a particular individual